La teoria molecolare di Ampère: una visione di primo Ottocento carica di stimoli di riflessione - Villani, Vincenzo (Chimica nella Scuola, 2025)
André-Marie Ampère (1775-1836) was a universal genius, ranging from mathematics, to physics, to chemistry. Encouraged by the chemist Berthollet, in 1814 he published an elaborate theory of molecular structure that took into account Gay-Lussac’s law of combination volumes “To provide the means of predicting a priori the fixed ratios according to which bodies combine, bringing their different combinations back to principles that would be the expression of a law of nature”. In this work he enunciated, independently of Avogadro (1811), the law of direct proportionality between the volume of a gas and the number of particles contained therein, independent of their nature. Based on the atomistic vision inaugurated by Newton (1704) and the theory of short-range molecular forces developed by Laplace (1806), Ampère developed a complex geometric-molecular theory that, starting from only two fundamental forms, the tetrahedron and the octahedron, constructed stable molecular structures in accordance with the law of combination volumes of reagents and products. Ampère’s theory was not welcomed by the chemists of the time, however it spread and introduced for the first time the stereochemical vision of molecules and reactions that was finally affirmed in the hypothesis of tetrahedral carbon by van’t Hoff and Le Bel (1874). These anticipations, eclipsed by the nineteenth-century positivism that rejected the existence of atoms and molecules, later returned in various forms and still retain an educational and epistemological value today.